Дослідження методів аналізу графів для вирішення задач комп’ютерного зору - Кошурников, Г. О. (ХНУРЕ, 2023)
This work explores the application of graph-based algorithms in image segmentation. Image segmentation is crucial technique in computer vision because it allows to extract meaningful information from images by dividing them into distinct parts or regions, which enables a wide range of applications such as object recognition, tracking, and image analysis. Correctly picked algorithm combination can significantly facilitate software development process. By leveraging graph algorithms for diagrams and plots segmentation and recognition, it is possible to push software development process on a new level of cost efficiency and effectiveness